EFEK SEDIAAN REBUSAN DAUN SIRIH HIJAU (Piper betle Linn.) TERHADAP HIDROFOBISITAS BAKTERI STREPTOCOCCUS MUTANS DAN STREPTOCOCCUS SOBRINUS - , PRAMITA DYAH PANGESTU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Streptococcus mutans and S. sobrinus are cariogenicbacteria.Hydrophobic surface ofS. mutans and S. sobrinus play an important role in the attachment of bacterialto the acquired pellicle on tooth surfaces. Green betel (Pipper betle Linn.) has known as a traditional medicine to treat toothache. It contains flavonoids, alkaloids, tanins, hydroxycavicol, phenolate compounds and essential oils.The aim of this study was to determine the effects of green betel leaf decoction to thehydrophobicity of S. mutansand S. sobrinus. Cell surface hydrophobicity of S. mutans and S. sobrinus was determined by microbial adhesion to hydrocarbon test.Ten percent of green betel leaf decocticon was added toS. mutans and S. sobrinus suspension. After being exposed to green betel leaf decocticon for 5 minutes, the hexadecane was then added to the bacterial suspension. The bacterial suspension was measured using aspectrophotometer at a wavelength of 550 nm.The data were analyzedby t-test independent test. T-test showed a significant difference of the hydrophobicity (p<0.05)of S.mutansandS.sobrinusafter beingexposed togreenbetelleaf decoction compared by distilled water. It indicates that 10% of green betel leaf decocticon(Pipper betle Linn.) decreases the hydrophobicity of S. mutans and S. sobrinus.